Thresholds for gully initiation and sedimentation in Mediterranean Europe - Vandekerckhove, L. (2011)
In Mediterranean areas the dynamics of gully development act as an important indicator of desertification. However, little is known about the influence of climate and land-use changes, and almost no field data exist to assess the sensitivity of a landscape to gully erosion. Two important components of gully erosion studies are the prediction of where gullies begin and where they end. To address some of these issues, topographical thresholds for gully initiation and sedimentation in six different Mediterranean study areas were established. Field measurements of local soil surface slope (S) and drainage-basin area (A) at the point of initiation of ephemeral gullies in intensively cultivated fields (five datasets) and permanent gullies in rangelands (three datasets) were carried out. A negative power relationship of the form S = aA−b was fitted through all datasets, and defined as the mean topographical threshold for gullying in the respective area. Topographically controlled slopes of sedimentation at the gully bottom were also measured. Compared to theoretical relationships for channel initiation by overland flow, relatively low values for b are obtained, suggesting a dominance of overland flow and an influence of subsurface flow. The influence of landsliding at steeper slopes appeared from the flattening of the overall negative trend in the higher slope range (S > 0·30) of the integrated dataset. Comparing the threshold lines of our datasets to the average trend lines through data found in literature revealed that vegetation type and cover could better explain differences in topographical thresholds level than climatic conditions. In cultivated fields, soil structure and moisture conditions, as determined by the rainfall distribution, are critical factors influencing topographical thresholds rather than daily rainfall amounts of the gully-initiating events. In rangelands, vegetation cover at the time of incision appears to be the most important factor differentiating between topographical thresholds, overruling the effect of average annual rainfall amounts. Soil texture and rock fragment cover contributed little to the explanation of the relative threshold levels. Differences in regression slopes (b) between the S–A relationships found in this study have been attributed to the soil characteristics in the different study areas, determining the relative importance of subsurface flow and Hortonian overland flow. Sedimentation slopes where both ephemeral and permanent gullies end were generally high because of the high rock fragment content of the transported sediment. A positive relationship was found between the rock fragment content at the apex of the sedimentation fan and the slope of the soil surface at this location. Copyright © 2000 John Wiley & Sons, Ltd.